Pengembangan Model Asuhan Keperawatan Gerontik untuk Meningkatkan Kualitas Hidup Lansia - Samila; Isymiarni Syarif Mila (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The elderly are an age group vulnerable to declines in physical, psychological, and social function, which impacts quality of life. Comprehensive geriatric nursing care is needed to improve the quality of life of the elderly. This study aims to develop an effective geriatric nursing care model for improving the quality of life of the elderly. The study used a quasi-experimental design with a pretest-posttest approach. The sample size was 50 elderly individuals. The results showed an improvement in the quality of life of the elderly after the implementation of the geriatric nursing care model. It was concluded that the geriatric nursing care model has an impact on improving the quality of life of the elderly.